Are We Reading Patch Test Reactions in a Uniform Way? An International Contact Dermatitis Research Group Study - Bruze, Magnus; Ale, Iris; Andersen, Klaus E.; Elsner, Peter; Goh, Chee Leok; Goossens, An; Jerajani, Hemangi; Maibach, Howard; Matsunaga, Kayoko; Nixon, Rosemary; Sasseville, Denis (Dermatitis, 2025)
Background: Concern was raised within the International Contact Dermatitis Research Group (ICDRG) regarding the scoring of weak allergic versus doubtful patch test reactions. Objective: To investigate the degree of uniformity in patch test reading. Methods: Five series of fictive contact dermatitis cases were written up by the study organizer and presented to expert participants. Each series was sent electronically to participants one by one. All dermatitis cases underwent patch testing, and the test result was a reaction characterized by erythema and infiltration. Within each case series, there were 5 subcases that differed only in the size of the test area showing erythema and infiltration. Three nearly identical case series had 1 crucial difference: the result of a repeated open application test (ROAT), both in the cases and controls. The experts had to determine whether the patch test reaction indicated contact allergy, defined as an immunologically acquired delayed hypersensitivity. All other reactions (negative, doubtful, and irritant) were classified as no contact allergy. Results: There was a big intra- and inter-individual variation in the patch test reading. Nobody read according to any of the 2 existing ICDRG classifications. The ROAT results sometimes influenced the scoring. Conclusion: A new ICDRG classification is needed.
Publisher Copyright: © 2025 American Contact Dermatitis Society. All Rights Reserved.